XIV International Conference Noise Control’07 Elbląg, Poland, June 3-6, 2007 - ZAWIESKA, Wiktor M. (Archives of Acoustics, 2007)
Noise Control is the most important international acoustics conference regularly organized in Poland. The XIV International Conference Noise Control’07 is taking place between June 3 and 6, 2007 in Elbląg. It is organized by the Central Institute for Labour Protection – National Research Institute, the Committee on Acoustics of the Polish Academy of Sciences, the Polish Acoustical Society, with the cooperation of the Department of Mechanics and Vibroacoustics of the AGH University of Science and Technology, and the Department of Acoustics of the Building Research Institute. Patrons of the Conference: – Ministry of Labour and Social Policy; – Ministry of the Environment; – Chief Labour Inspectorate.